The economic cost of failure in clinical education: a multi‐perspective analysis. Issue 7 (21st March 2017) - Foo, Jonathan; Rivers, George; Ilic, Dragan; Evans, Darrell J R; Walsh, Kieran; Haines, Terrence; Paynter, Sophie; Morgan, Prue; Lincke, Karl; Lambrou, Haria; Nethercote, Anna; Maloney, Stephen
Abstract : Context: Failure by students in health professional clinical education intertwines the health and education sectors, with actions in one having potential downstream effects on the other. It is unknown what economic costs are associated with failure, how these costs are distributed, and the impacts these have on students, clinicians and workplace productivity. An understanding of cost drivers and cost boundaries will enable evidence‐based targeting of strategic investments into clinical education, including where they should be made and by whom. Objectives: This study was designed to determine the additional economic costs associated with failure by students in health professional clinical education. Methods: A cost analysis study involving cost identification, measurement, valuation and the calculation of total cost was conducted. Costs were considered from the perspective of the student, the education institution, the clinical educator, the health service placement provider organisation and the government. Data were based on a 5‐week clinical education programme at Monash University, Australia. Data were collected using quantitative surveys and interviews conducted with health professional students, clinical educators and education institute staff. Reference group representation was also sought at various education institution and health service organisation levels. A transferable model with sensitivity analysis was developed. Results: There is a total additional cost of US$9371 per student failing in clinical education from the perspective of all stakeholders considered. Students bear the majority of this burden, incurring 49% of costs, followed by the government (22%), the education institution (18%), the health service organisation (10%) and the clinical educator (1%). Conclusions: Strong economic links for multiple stakeholders as a result of failure by students in clinical education have been identified. The cost burden is skewed in the direction of students. Any generalisation of these results should be made with consideration for the unique clinical education context in which each health professional education programme operates.